Optimizations and comparison of three two-stage Rankine cycles under different heat source temperatures and NG distribution pressures. (1st April 2020) - Sun, Zhixin; Zhang, Han; Zhang, Tianfeng; Lin, Li; Lin, Kui
Highlights: Three two-stage Rankine cycles with direct expansion are compared. Fluids with high critical and low normal boiling temperatures are better. A maximum efficiency of 30.54% is achieved by ammonia. Two-condensation ORC is both the best thermodynamic and economic systems. The systems could greatly reduce CO2 emission. Abstract: Two-stage Rankine cycles draw more and more attention with the increasing trade of LNG (liquefied natural gas) and the recovery of both the cold exergy of LNG and the thermal exergy of low temperature heat source. To figure out the best configuration of two-stage Rankine cycles, three mostly studied configuration, cascade two-stage ORC (organic Rankine cycle), parallel two-stage ORC and two-condensation ORC are optimized and compared under different heat source temperatures and different NG distribution pressures. Ten substances are selected as the working fluids. The evaporation, condensation and expander inlet temperatures of both ORCs and the LNG regasification pressure are optimized to obtain the maximum exergy efficiency. The results show that both the increase of heat source temperature and the decrease of NG distribution pressure can improve the exergy efficiencies greatly. The increase of heat source temperature not only increases the optimal key parameters but also affects the ranking of optimal fluids, while the increase of NG distribution pressure only affects the optimal parameters. Different from conventional Rankine cycles, there is also an optimal condensation temperature to match the heat absorption line of LNG and it increases with increase of the NG distribution pressure. The LNG regasification pressure is a key parameter which determines the proportion of power outputs between ORCs and direct expansion cycles. The thermodynamic performances of parallel two-stage ORC and two-condensation ORC are almost the same, which are obviously better than that of cascade two-stage ORC. Both parallel two-stage ORC and two-condensation ORC with ammonia as the working fluid achieve the maximum efficiency of 30.54% under the heat source temperature of 200 ℃ and the NG distribution pressure of 3 MPa. Two-condensation ORC is the optimum configuration with both good thermodynamic and economic performances. The lowest electricity production cost of two-condensation ORC achieved in this paper is 0.033$/kW·h. The environmental side effect caused by working fluid leakage is negligible compared with the saved CO2 emission via the electricity generation.